2020
DOI: 10.1101/2020.02.13.947549
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global Dynamic Molecular Profiles of Stomatal Lineage Cell Development by Single-Cell RNA Sequencing

Abstract: 30The regulation of stomatal lineage cell development has been extensively investigated. 31 However a comprehensive characterization of this biological process based on 32 single-cell transcriptome analysis has not yet been reported. Here, we performed 33 RNA-seq on over 12,844 individual cells from the cotyledons of five-day-old 34 Arabidopsis seedlings. We identified 11 cell clusters corresponding mostly to cells at 35 specific stomatal developmental stages with a series of new marker genes. 36 Comp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 83 publications
(134 reference statements)
1
9
0
Order By: Relevance
“…We could not identify TCs by the expression of the TC marker gene GL2 because the size of TCs was too large to pass through the cell strainer. In our previous study, we found that some marker genes were detected in several cell types but at different levels of expression (Liu et al, 2020). The top 10 marker genes for each of the studied cell types other than TCs were specifically expressed in the corresponding cell types, except for the markers of MPCs, GMCs, and GCs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We could not identify TCs by the expression of the TC marker gene GL2 because the size of TCs was too large to pass through the cell strainer. In our previous study, we found that some marker genes were detected in several cell types but at different levels of expression (Liu et al, 2020). The top 10 marker genes for each of the studied cell types other than TCs were specifically expressed in the corresponding cell types, except for the markers of MPCs, GMCs, and GCs.…”
Section: Resultsmentioning
confidence: 99%
“…Pseudo-time trajectory analysis of single-cell transcriptomes was conducted using Monocle 2 (Trapnell et al, 2014) as previously described (Liu et al, 2020).…”
Section: Pseudo-time and Trajectory Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…These studies demonstrated the remarkable power of scRNA-Seq to detect rare cell types/states and to resolve developmental trajectories in a complex tissue. Subsequent studies have diversified to applying this technique to examine the development of stomata [15,16], leaf vasculature [17,18], shoot apices [19][20][21], inflorescences [22], and lateral root primordia [23], in species such as arabidopsis, maize (Zea mays), rice (Oryza sativa), and tomato (Solanum lycopersicum) (Table 1). Together, these early studies have provided unique insights into the processes of differentiation [4,6,9], tissue-specific abiotic stress responses [5,24], cell-type-specific responses to genetic perturbations [4,6,8,19], and cell-cycle regulator dynamics [16,21], thus providing a strong examination of the virtues of utilizing the technology in plants (Table 1).…”
mentioning
confidence: 99%